Mark Fisher and reimagining postcapitalist geographies. Issue 1 (March 2023) - Sutherland, Callum
In this paper, I outline the spatial imaginaries of the late radical thinker Mark Fisher (1968–2017). I begin by explaining Fisher's focus on culture and desire as forces that must be addressed if an effective postcapitalist politics is to be formed and underscoring that so far in postcapitalist geographies, the roles of culture and desire have been relatively overlooked. I then delineate three spatial imaginaries threaded through Fisher's work, which I call 3D hauntology, grotesque stratigraphy, and acid topology, demonstrating how they offer fresh ideas at the nexus of postcapitalist geography and political strategy. To conclude, I argue that postcapitalist geographers must urgently foster cultural and political experiments that wager on latent popular desire for a future characterised by a reimagined communism.